First case of ductal adenocarcinoma of the prostate with MAP3K1 homozygous deletion. Issue 3 (17th March 2021) - Shojo, Kazunori; Kosaka, Takeo; Nakamura, Kohei; Hongo, Hiroshi; Kobayashi, Hiroaki; Mikami, Shuji; Nishihara, Hiroshi; Oya, Mototsugu
Abstract : Introduction: Ductal adenocarcinoma of the prostate is a rare prostate cancer variant and associated with higher stage and greater risk of mortality. Optimal systemic therapy for metastatic ductal adenocarcinoma is not known. Case presentation: A 67‐year‐old man presented with ductal adenocarcinoma of the prostate accompanied by multiple lung metastases and advanced bone metastases. We performed channel transurethral resection of the prostate and confirmed the diagnosis of ductal adenocarcinoma of the prostate. DNA sequencing identified a TP53 somatic point mutation (p.Gly245Ser) as the pathogenic variant. Furthermore, a homozygous deletion was observed in mitogen‐activated protein kinase kinase kinase 1. The patient received enzalutamide but deceased 5 months after presenting to our institution. Conclusion: To our knowledge, this is the first report of ductal adenocarcinoma of the prostate with a mitogen‐activated protein kinase kinase kinase 1 homozygous deletion. Accumulation of whole‐exome sequencing data is expected to inform future advances in therapy development.